Prevalence of Yersinia enterocolitica from food and pigs in selected states of Malaysia - Tan, Lai Kuan; Ooi, Peck Toung; Thong, Kwai Lin (Elsevier, 2014)
The aim of this study was to determine the prevalence of Yersinia enterocolitica and its bioserotypes from food and pigs in Malaysia. Fifty-eight raw porcine (raw pork meat, internal organs and other parts) and 48 non-porcine food (raw beef, poultry products, seafood, vegetables, tofu, and pasteurised milk) from wet markets located in Kuala Lumpur, Selangor, Perak, and Pahang were examined for the presence of Y. enterocolitica. Specimens (nasal, oral and rectal swabs) from 165 pigs (from nine farms) located at central and northern parts of Malaysia were also collected for Y. enterocolitica detection. Presumptive isolates were characterised biochemically and further confirmed by PCR. Out of 58 raw porcine food, Y. enterocolitica was detected in 7 (12.1%) samples in which raw pork meat (whole meat) had the highest prevalence 5/21 (23.8%), followed by raw pork liver 1/5 (20.0%) and raw pork intestine 1/8 (12.5%). No Y. enterocolitica was isolated from the 48 non-porcine foods. Overall, two pathogenic (bioserotypes 3 variant/O:3 and 1B/O:8) and one non-pathogenic (bioserotype 1A/O:5) Y. enterocolitica strains were isolated from food. Out of 165 pigs examined, 3 (1.8%) pigs were carriers for Y. enterocolitica. All 3 pigs were asymptomatic grower pigs from Penang, carried Y. enterocolitica bioserotype 3 variant/O:3. Post-enrichment PCR approach gave a higher prevalence, 60.3%, 41.7% and 27.9% for porcine food, non-porcine food and pigs, respectively. Both pathogenic and non-pathogenic Y. enterocolitica were present in our domestic pigs and food. Improper food handling and processing may cause cross contamination of this pathogen to humans, affirms a potential risk for public health.